MATHEMATICAL ANXIETY OF ELEMENTARY STUDENTS DURING THE COVID-19 PANDEMIC - Riska Nurhasanah; Tatang Herman; Aan Yuliyanto; Hanifah Nuryani (Department of Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Alauddin Makass, 2022)
Abstract This study aimed to describe the students' mathematical anxiety during online learning at a private elementary school in Bandung, Indonesia. This research used a quantitative method. The subjects of this study were 28 fifth-grade students, a teacher, and students’ parents. The instruments were questionnaires for students and an interview list for the teacher and parents. The data was then analyzed quantitatively and descriptively through tables and charts. The result indicated that each aspect of mathematical anxiety in this study showed a low category for affective and high for cognitive and somatic aspects. The anxiety of elementary school students should be a particular concern for teachers in carrying out learning so as not to interrupt the learning process.